2019
DOI: 10.3390/ijerph16132433
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Traffic-Related Air Pollution: Case Study of Pregnant Women in South Texas

Abstract: Population groups vulnerable to adverse effects of traffic-related air pollution correspond to children, pregnant women and elderly. Despite these effects, literature is limited in terms of studies focusing on these groups and a reason often cited is the limited information on their mobility important for exposure assessment. The current study presents a method for assessing individual-level exposure to traffic-related air pollution by integrating mobility patterns tracked by global positioning system (GPS) de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…If air pollution occurs in certain seasons and areas, such as in China [80], people are more likely to have vitamin D deficiency. Additionally, previous studies also reported that PM 2.5 could directly cause many chronic diseases, such as respiratory and cardiovascular diseases, to which children, pregnant women, and elderly individuals are more susceptible [81]- [83]. The doubly harmful effects of PM 2.5 deserve our attention.…”
Section: Discussionmentioning
confidence: 97%
“…If air pollution occurs in certain seasons and areas, such as in China [80], people are more likely to have vitamin D deficiency. Additionally, previous studies also reported that PM 2.5 could directly cause many chronic diseases, such as respiratory and cardiovascular diseases, to which children, pregnant women, and elderly individuals are more susceptible [81]- [83]. The doubly harmful effects of PM 2.5 deserve our attention.…”
Section: Discussionmentioning
confidence: 97%
“…Children, older adults, and pregnant women are especially vulnerable to the health effects of air pollution [5][6][7]. PM10 [8,9] and PM2.5 [8,10,11] have been shown to be associated with the development and worsening of asthma in about 10% of children worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Fine particulate matter (PM 2.5 ) is a U.S. Environmental Protection Agency (EPA) regulated criteria air pollutant [7]. PM 2.5 is emitted from different emission sources including the transportation sector, and studies have demonstrated elevated PM 2.5 concentrations in near-road environments [8][9][10][11][12]. A growing body of literature shows associations between higher exposure to PM 2.5 , due to proximity of residential areas to major roadways and adverse health effects [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%